Penerapan Pembelajaran Model Latihan Shadwo dalam Permainan Tenismeja di SMA Negeri 6 Kabupaten Tana Toraja - Nurlati Syamsuddin; Nurul Musfira; Nurussyariah Hammado (Universitas Negeri Makassar, 2020)
The application of the Shadwo training model socialization in the tennis game directly helped the tennis trainer to be able to utilize the available facilities to activate the athlete as a whole in the training practice process that was carried out at SMA Negeri 6 Tana Toraja. In addition, students indirectly realize that they will acquire skills that can support their ability to play tennis. Thus it can provide motivation to students to learn and practice so that they can play tennis well. The benefits of using the Shadwo training method in practicing jasmine can increase the quantity and quality of the ball that can be received in a short time. No time is wasted thinking when picking up the ball once it starts to rally and it is often easier for the coach to direct the ball to the right place, multiball is very useful for improving footwork, power, speed, reaction time, endurance and anticipation. And multiball is great for trying new things because it eliminates the fear of failure. This can help players trust and encourage development. Related to this, it can improve the ability of students so that students of SMA Negeri 6 Tana Toraja are able to play tennis. SMA Negeri 6 Tana Toraja Regency is a national level school, supported by very adequate facilities such as; fully equipped rooms and laboratories (chemical laboratories, physics laboratories, biology laboratories, computer laboratories, and language laboratories). In addition to this, the potential of human resources (teachers) is very supportive because they have participated in national-level training. On the other hand students at the school, support such as facilities and potential teachers are very well utilized. This is due to students going through the screening system as practiced by public schools in Tana Toraja Regency. Students who enter are students who are netted and have high intellectual and average family economic status. The school has an area of 11034 M with a total of 28 teachers, 425 students. Sports facilities at the Tana Toraja State High School are basketball courts, takraw fields, badminton fields and tennis courts.The importance of sport is felt by humans in their daily activities. Many kinds of sports, one of which is table tennis. Table tennis is a sport that has many fans, not limited to the level of adolescence, but also children and parents, men and women are quite large in demand. This is because the game of table tennis is not too complicated to learn. Someone who wants to play table tennis well must learn basic techniques such as stroke or stroke. One type of punch that needs to be mastered is forehand and backhand.One way to realize the success of teaching and learning activities is the selection of appropriate and efficient learning methods and media, so students can receive and understand the subject matter. The position of the learning method in teaching and learning activities is very important.